A novel tooth surface modification methodology for wide-faced double-helical gear pairs. (June 2021) - Yuan, Bing; Liu, Geng; Yue, Yanjiong; Liu, Lan; Shen, Yunbo
Highlights: Established a quasi-static multi-point contact analysis model for double-helical gear system. Determined the mesh misalignment caused by system flexibility and compensated tooth surface modification. Established a multi-objective optimization mathematical model of tooth surface modification. Combining compensated tooth surface modification and multi-objective optimization modification. Abstract: Aiming to improve the meshing quality of tooth surface and reduce the system vibration, a novel tooth surface modification methodology for the wide-faced double-helical gear pairs is developed in consideration of system flexibility. The quasi-static multi-point contact analysis model for double-helical gear system is established based on the new concept of axial multi-point contact and the substructure technique. The mesh misalignment caused by system flexibility and the compensated tooth surface modification parameters can be determined. Also, a multi-objective optimization mathematical model of tooth surface modification is established in order to reduce the fluctuation of vibration exciting force and improve the load distribution. The Pareto frontier solutions of tooth surface modification parameters are obtained by combining the loaded tooth contact analysis(LTCA) model and the NSGA-II algorithm. The final modified tooth surface for wide-faced double-helical gear pairs is obtained using the combination of compensated tooth surface modification and multi-objective optimization modification. The influences of system flexibility and tooth surface modification on quasi-static behaviors of the wide-faced double-helical gear pairs are discussed.